Analisis Gaya Belajar Siswa Terhadap Hasil Belajar Pendidikan Agama Kristen - Bambang Sujiyono (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2021)
The purpose of the study was to analyze students' learning styles and their relationship to students' learning outcomes in Christian religious lessons. The study of literature became the method used. The study findings revealed that students' learning styles have a close relationship with learning outcomes. Where the right student learning style will help students in understanding the subject matter, as well as can improve student learning outcomes in school. The role of Christian teachers in schools is very important in providing guidance and direction for students in learning, both when studying at school and at home. The attention and guidance of Christian teachers is essential for students in achieving better learning outcomes. Tujuan dari penelitian ini ialah untuk menganalisis gaya belajar siswa dan kaitannya dengan hasil belajar siswa dalam pelajaran agama Kristen. Studi literatur menjadi metode yang digunakan. Temuan penelitian mengungkapkan bahwa gaya belajar siswa memiliki hubungan yang erat dengan hasil belajar. Dimana gaya belajar siswa yang tepat akan membantu siswa dalam memahami materi pelajaran, serta dapat meningkatkan hasil belajar siswa di sekolah. Peran guru agama Kristen di sekolah sangat penting dalam memberikan bimbingan dan arahan bagi siswa dalam belajar, baik ketika belajar di sekolah maupun di rumah. Perhatian dan bimbingan guru agama Kristen sangat penting bagi siswa dalam mencapai hasil belajar yang lebih baik.